Prospective study of etiology of liver abscess and comparison of different ways of its management - Jaiswal, Anand Kumar; Jain, R. K.; Sarin, Rahul (International Surgery Journal, 2020)
Background: Liver abscess is a collection of purulent material in the liver parenchyma which can be due to bacterial, parasitic, fungal or mixed infection. It has become one of the most common communicable disease with much more prevalence in underdeveloped and developing countries. Two most common type of liver abscess are amoebic and pyogenic. Pyogenic liver abscess is more common in western world while amoebic liver abscess is more commonly found in third world countries, which are under developed, and more people living under lower socio economic conditions. Methods: A prospective study of 50 patients with clinical diagnosis of liver abscess admitted in the department of surgery B. R. D. Medical College Gorakhpur during a period of one year. Results: There was male predominance (98%) and most of the patient belongs to younger age group and low socio economics status. In amoebic liver abscess there was strong correlation with alcohol intake (66%). Conclusions: In our study most of the patients were group 21-30 years and the most common presenting symptom was right upper quadrant pain and fever. In most of the patients, the common hematological finding was mild anaemia with leucocytosis with altered LFT.